Investigating the Antioxidant Characteristics of Saccharina Latissima and Its Ability to Reduce Inflammation in RAW 264.7 Cells (P06-091-19). (13th June 2019) - Wiegand, Abigail; Grebe, Gretchen; Byron, Carrie; Myracle, Angela
Abstract: Objectives: The goal of this study is to understand the anti-inflammatory characteristics of Saccharina latissima (sugar kelp). Sugar kelp is a brown macroalga that grows readily off the coast of Maine. Other seaweeds are known to contain bioactive chemicals that reduce inflammation—a contributing factor to metabolic syndrome and type 2 diabetes. It is hypothesized that injuring farmed sugar kelp by trimming the kelp may increase the beneficial bioactives and promote anti-inflammatory effects. The specific aims are (1) to produce extracts of Maine-grown sugar kelp through accelerated solvent extraction (ASE), (2) to measure the samples' antioxidant capacity, and (3) to investigate the samples' anti-inflammatory effect in vitro . Methods: Sugar kelp samples were freeze-dried and extracts were produced using ASE. Total phenolic content was measured using the Folin-Ciocalteau assay, and radical scavenging capacity was measured with a 2, 2-diphenyl-1-picrylhydrazyl (DPPH) assay. The sugar kelp extracts were tested for cytotoxicity in RAW 264.7 macrophages using a 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2H-tetrazolium bromide (MTT) assay. Lipopolysaccharide (LPS) was used to induce inflammation in the cells, and the attenuation effect of extract doses ranging from 12.5–50 µg total phenolics (TP)/mL was observed by measuring nitric oxide (NO) secretion with the Griess assay. Results: Preliminary data shows that sugar kelp contains polyphenols (8.4–16.0 mg gallic acid equivalent/g dried biomass) and radical scavenging capacity (IC50 = 61.8–79.5 µg/mL). The data did not demonstrate the trimming the kelp has a beneficial effect to increase phenolic compounds. The polyphenolic contents of the trimmed samples were lower than the untrimmed (9.5 vs. 13.1 mg gallic acid equivalent/g dried biomass). The radical scavenging capacity decreased when the samples were trimmed (14.7%). The greatest decrease in NO production was at a concentration of 50 μg TP/mL for a trimmed sample (up to 78.5%), which supports the hypothesis. Conclusions: This data suggests that sugar kelp may be a good source of antioxidants and trimmed samples may contain additional bioactives to help decrease inflammation. Further investigation is needed to confirm the hypothesis. Funding Sources: The University of Maine The University of New England